How to determine the time needed to dry the drainage layer of airdrome pavement - Ципріанович, І. В.; Баришпол, А. І. (Proceedings of National Aviation University, 1998)
In order to further improve the normative basis of airdrome pavement projecting for increasing it efficiency considered is the problem of determining the time needed to dry the drainage layer, its capacity and hydraulic slope and to obtain the best economic results. Here we give the results which can be used for substantiation and perfection of airdromes pavement norms, also for hydrogeological calculation of drainage pavements with increased efficiency of draining the surface and subterranean water